Deep reflection seismic imaging of iron‐oxide deposits in the Ludvika mining area of central Sweden - Malehmir, Alireza (Uppsala University, 2021)
Reflection seismic data were acquired within two field campaigns in the Blötberget, Ludvika mining area of central Sweden, for deep imaging of iron‐oxide mineralization that were known to extend down to 800–850 m depth. The two surveys conducted in years 2015 and 2016, one employing a seismic landstreamer and geophones connected to wireless recorders, and another one using cabled geophones and wireless recorders, aimed to delineate the geometry and depth extent of the iron‐oxide mineralization for when mining commences in the area. Even with minimal and conventional processing approaches, the merged datasets provide encouraging information about the depth continuation of the mineralized horizons and the geological setting of the study area. Multiple sets of strong reflections represent a possible continuation of the known deposits that extend approximately 300 m further down‐dip than the known 850 m depth obtained from historical drilling. They show excellent correlation in shape and strength with those of the Blötberget deposits. Furthermore, several reflections in the footwall of the known mineralization can potentially be additional resources underlying the known ones. The results from these seismic surveys are encouraging for mineral exploration purposes given the good quality of the final section and fast seismic surveys employing a simple cost‐effective and easily available impact‐type seismic source.

The datasets consist of processed unmigrated stacked sections. One mixed file for 2015 and 2016 (see Markovic et al., 2020 and Malehmir et al., 2017) and one file for 2016 (see Markovic et al., 2020).

Data are available in SEG-Y format and can be read in 3D visualization software such as GOCAD. Examples of free non-proprietary programs that can be used are ssView (https://sourceforge.net/projects/simple-seismic/) and SeisSee (https://seisee.software.informer.com/).

Additional data can be made available upon request. The additional data are raw shot gathers unprocessed but contains coordinates and information to process them using common seismic processing software.

These key references should be cited when reusing data:

Malehmir, A., Maries, G., Bäckström, E., Schon, M., & Marsden, P. (2017). Deep Targeting an Iron-Oxide Ore Body Using a Seismic Landstreamer and a 500-Kg Drop Hammer Source. 79th EAGE Conference and Exhibition 2017.

Bräunig, L., Buske, S., Malehmir, A., Bäckström, E., Schön, M., and Marsden, P., 2020. Seismic depth imaging of iron-oxide deposits and their host rocks in the Ludvika mining area of central Sweden. Geophysical Prospecting, 68, 24–43.

Markovic, M., Maries, G., Malehmir, A., von Ketelholdt, J., Bäckström, E., Schön, M., and Marsden, P., 2020. Deep reflection seismic imaging of iron-oxide deposits in the Ludvika mining area of central Sweden. Geophysical Prospecting, 68, 7–23.

Balestrini, F., Draganov, D., Malehmir, A., Marsden, P., and Ghose, R., 2020. Improved target illumination at Ludvika mines of Sweden through seismic-interferometric surface‐wave suppression. Geophysical Prospecting, 68, 200–213.

Papadopoulou, M., Da Col, F., Mi, B., Bäckström, E., M., Marsden, P., Malehmir, A., and Socco, L. V., 2020. Surface-wave analysis for static corrections in mineral exploration: A case study from central Sweden. Geophysical Prospecting, 68, 214–231.

Malehmir, A., Maries, G., Bäckström, E., Schön, M., and Marsden, P., 2017. Developing cost-effective seismic mineral exploration methods using a landstreamer and a drophammer. Nature Scientific Reports, 7, 10325.

Maries, G., Malehmir, A., and Marsden, P., 2020. Cross-profile seismic data acquisition, imaging and modeling of iron-oxide deposits: a case study from Blötberget, south central Sweden. Geophysics, 85, B219– B233.

Reflection seismic data were acquired within two field campaigns in the Blötberget, Ludvika mining area of central Sweden, for deep imaging of iron‐oxide mineralization that were known to extend down to 800–850 m depth. The two surveys conducted in years 2015 and 2016, one employing a seismic landstreamer and geophones connected to wireless recorders, and another one using cabled geophones and wireless recorders, aimed to delineate the geometry and depth extent of the iron‐oxide mineralization for when mining commences in the area. Even with minimal and conventional processing approaches, the merged datasets provide encouraging information about the depth continuation of the mineralized horizons and the geological setting of the study area. Multiple sets of strong reflections represent a possible continuation of the known deposits that extend approximately 300 m further down‐dip than the known 850 m depth obtained from historical drilling. They show excellent correlation in shape and strength with those of the Blötberget deposits. Furthermore, several reflections in the footwall of the known mineralization can potentially be additional resources underlying the known ones. The results from these seismic surveys are encouraging for mineral exploration purposes given the good quality of the final section and fast seismic surveys employing a simple cost‐effective and easily available impact‐type seismic source.

The datasets consist of processed unmigrated stacked sections. One mixed file for 2015 and 2016 (see Markovic et al., 2020 and Malehmir et al., 2017) and one file for 2016 (see Markovic et al., 2020).

Data are available in SEG-Y format and can be read in 3D visualization software such as GOCAD. Examples of free non-proprietary programs that can be used are ssView (https://sourceforge.net/projects/simple-seismic/) and SeisSee (https://seisee.software.informer.com/).

Additional data can be made available upon request. The additional data are raw shot gathers unprocessed but contains coordinates and information to process them using common seismic processing software.

These key references should be cited when reusing data:

Malehmir, A., Maries, G., Bäckström, E., Schon, M., & Marsden, P. (2017). Deep Targeting an Iron-Oxide Ore Body Using a Seismic Landstreamer and a 500-Kg Drop Hammer Source. 79th EAGE Conference and Exhibition 2017.

Bräunig, L., Buske, S., Malehmir, A., Bäckström, E., Schön, M., and Marsden, P., 2020. Seismic depth imaging of iron-oxide deposits and their host rocks in the Ludvika mining area of central Sweden. Geophysical Prospecting, 68, 24–43.

Markovic, M., Maries, G., Malehmir, A., von Ketelholdt, J., Bäckström, E., Schön, M., and Marsden, P., 2020. Deep reflection seismic imaging of iron-oxide deposits in the Ludvika mining area of central Sweden. Geophysical Prospecting, 68, 7–23.

Balestrini, F., Draganov, D., Malehmir, A., Marsden, P., and Ghose, R., 2020. Improved target illumination at Ludvika mines of Sweden through seismic-interferometric surface‐wave suppression. Geophysical Prospecting, 68, 200–213.

Papadopoulou, M., Da Col, F., Mi, B., Bäckström, E., M., Marsden, P., Malehmir, A., and Socco, L. V., 2020. Surface-wave analysis for static corrections in mineral exploration: A case study from central Sweden. Geophysical Prospecting, 68, 214–231.

Malehmir, A., Maries, G., Bäckström, E., Schön, M., and Marsden, P., 2017. Developing cost-effective seismic mineral exploration methods using a landstreamer and a drophammer. Nature Scientific Reports, 7, 10325.

Maries, G., Malehmir, A., and Marsden, P., 2020. Cross-profile seismic data acquisition, imaging and modeling of iron-oxide deposits: a case study from Blötberget, south central Sweden. Geophysics, 85, B219– B233.
Deep reflection seismic imaging of iron‐oxide deposits in the Ludvika mining area of central Sweden
Keywords: Mineral resources; Mineralfyndigheter; Exploration; Exploration; Survey; Survey; Seismic; Seismic; Mineral; Mineral; processing; Processing; Innovation; Innovation; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Geology; Geologi; Geophysics; Geofysik; Geoscientific Information; Geovetenskap